Radiosynthesis of (R,S)‐[(18)F]GE387: A Potential PET Radiotracer for Imaging Translocator Protein 18 kDa (TSPO) with Low Binding Sensitivity to the Human Gene Polymorphism rs6971 - Qiao, Luxi (ChemMedChem, 2019)
Translocator protein (TSPO) is a biomarker of neuroinflammation, which is a hallmark of many neurodegenerative diseases and has been exploited as a positron emission tomography (PET) target. Carbon‐11‐labelled PK11195 remains the most applied agent for imaging TSPO, despite its short‐lived isotope and low brain permeability. Second‐generation radiotracers show variance in affinity amongst subjects (low‐, mixed‐, and high‐affinity binders) caused by the genetic polymorphism (rs6971) of the TSPO gene. To overcome these limitations, a new structural scaffold was explored based on the TSPO pharmacophore, and the analogue with a low‐affinity binder/high‐affinity binder (LAB/HAB) ratio similar (1.2 vs. 1.3) to that of (R)‐[(11)C]PK11195 was investigated. The synthesis of the reference compound was accomplished in six steps and 9 % overall yield, and the precursor was prepared in eight steps and 8 % overall yield. The chiral separation of the reference and precursor compounds was performed using supercritical fluid chromatography with >95 % ee. The absolute configuration was determined by circular dichroism. Optimisation of reaction conditions for manual radiolabelling revealed acetonitrile as a preferred solvent at 100 °C. Automation of this radiolabelling method provided R and S enantiomers in respective 21.3±16.7 and 25.6±7.1 % decay‐corrected yields and molar activities of 55.8±35.6 and 63.5±39.5 GBq μmol(−1) (n=3). Injection of the racemic analogue into a healthy rat confirmed passage through the blood–brain barrier.